Monitoring Poverty in Uttar Pradesh : A Report on the Second Poverty and Social Monitoring Survey - Government of Uttar Pradesh; World Bank (World Bank, Washington, DC, 2014)
The report aims to provide a quick statistical update on changes in poverty and living conditions and access to services between the two periods of February and June 200, and 2002-2003, the two data points. At the same time, the Government of Uttar Pradesh requested the Bank's support for a preparation of a joint report with a wider and deeper scope of analysis focusing on determinants and changes in living conditions of the Uttar Pradesh population and assessing performance of current policies and programs with respect to their impacts on the poor. This report highlights income and poverty trends between 1993/94 and 2002/03, education trends between 1999/2000 and 2002/03, health trends in the late 1990s-early 2000), access to amenities trends between 1999/2000 and 2002/03, and government program trends between 1999/2000 and 2002/03.